BRAZILIAN YEARBOOK OF BASIC EDUCATION 2020 AND ITS RELATIONSHIP WITH EDUCATIONAL POLICIES (VERUM: Journal of Scientific Initiation, 2021)
This paper aims to provide a brief summary of Basic Education and Higher Education in Brazil, considering the data collected by the 2020 Brazilian Yearbook of Basic Education. It presents insights, guidelines, deficiencies, and potential areas for reflection regarding education. What is interesting about this document is that, in addition to providing precise and current data, it also allows for an analysis that integrates various data and categories, such as issues related to school access, educational trajectories, teaching modalities and stages, and matters regarding the general profile of teachers and students. It also covers topics such as learning, school management, and funding.
Keywords: Yearbook 2020; Basic Education; Higher Education; Public Policies